Sepulturas escavadas na rocha de Entre Douro e Minho - Barroca, Mário Jorge (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
Written in 1987 and revised in 1990, the present study, dedicated to the rock-hewn tombs of the Entre Douro e Minho, brings a contextualized perspective of these medieval archaeological remains. It was, in this perspective, a pioneer study in Portugal. First we analyze the earliest historical references for this kind of graves and the various chronological proposals suggested by the different authors. Then we develop the theory of Alberto del Castillo, and his chronological and typological proposals. We also discuss the contributions of recent authors and the problematic related with these graves. Finally, we present an overview of these graves evolution in the Entre Douro e Minho and an archaeological inventory for the three districts of this region (Viana do Castelo, Braga and Porto)